2014
DOI: 10.1071/rd12222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spermatozoa–oviductal cell coincubation time and oviductal cell age on spermatozoa–oviduct interactions

Abstract: Abstract. The oviduct plays a crucial role in sperm storage, maintenance of sperm viability and sperm transport to the site of fertilisation. The aim of the present study was to investigate the effects of oviductal cell culture passage number, oviductal cell age and spermatozoa-oviduct coincubation times on gene expression in oviductal cells. Immortalised oviductal epithelial cells (OPEC) obtained from two different cell passages (36 and 57) were subcultured three times with and without spermatozoa for 24 h (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…In conclusion, the present study shows for the first time that boar spermatozoa alter the expression of HSP genes directly, quickly, and markedly in co‐cultured OECs, and that an individual boar ejaculate effect exists. Our results confirm previous reports assessing protein expression in vitro (Ellington et al, ), and lead us to accept that oviductal monolayers present a useful model for studying sperm physiology within the oviduct, in agreement with Aldarmahi et al (, ). More research is warranted to evaluate if the absence of in vivo oviductal milieu (stroma and steroid hormones) has any impact on the ability of OECs to be influenced by the presence of sperm.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In conclusion, the present study shows for the first time that boar spermatozoa alter the expression of HSP genes directly, quickly, and markedly in co‐cultured OECs, and that an individual boar ejaculate effect exists. Our results confirm previous reports assessing protein expression in vitro (Ellington et al, ), and lead us to accept that oviductal monolayers present a useful model for studying sperm physiology within the oviduct, in agreement with Aldarmahi et al (, ). More research is warranted to evaluate if the absence of in vivo oviductal milieu (stroma and steroid hormones) has any impact on the ability of OECs to be influenced by the presence of sperm.…”
Section: Discussionsupporting
confidence: 93%
“…The observation made herein, that HSP gene expression is only markedly upregulated when spermatozoa are in direct contact with OECs rather than when they are kept separate using diffusible membrane inserts, tends to support this view. In agreement with other studies (Aldarmahi et al, 2012, 2014), we thus propose that spermatozoa binding directly to OECs in co‐culture activates a specific signal transduction pathway within the OECs that results in the upregulation of HSP gene expression. HSPs synthesized de novo in response to sperm appear to translocate from within OECs to the oviductal lumen (Georgiou et al, ) and interact directly with the sperm membrane, probably through cholesterol molecules and/or lipid rafts that are present/accessible in uncapacitated but not in capacitated spermatozoa (Moein‐Vaziri et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specific features and functions of the oviductal epithelium are lost during in vitro culture [ 2 ]. Some studies showed that an increased number of oviduct culture passages resulted in decreased expression of several genes [ 8 15 ]. In addition, cell morphology alterations have also been reported with continuous cell culture [ 16 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome data indicated significant divergence of cell lines from their initial primary cells [ 20 , 21 ]. In addition, number of passaging strongly effects the mRNA expression of porcine oviductal cells [ 22 ] and of human synovial fibroblasts [ 23 ]. In this context, cell culture passaging also influences cellular responses by significantly reducing the expression rate of different proteins in synovial and gingival fibroblast cells [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%